Report of a Working Group on Forages: Ninth meeting, 23-25 October 2007, Piestany, Slovakia - Boller, B.; Wilner, E.; Marum, P.; Maggioni, L.; Lipman, E. (2010)
On 23-25 October 2007 the Research Institute of Plant Production (RIPP) of the Slovak Agricultural Research Centre hosted the Ninth meeting of the Working Group (WG) on Forages. The meeting, attended by 35 participants from 28 countries, focused on the ongoing effort to create a European Forages Collection. The ECPGR Poa and Phleum databases were analyzed to identify duplicate accessions and to define the primary holders of accessions to be included in the European Forages Collection. Another highlight of the meeting was the discussion on the results of the EU-funded Fifth Framework project on “Improving germplasm conservation methods for perennial European forage species” (ICONFORS) and the influence that these findings should have on the regeneration guidelines agreed by the Group. The Group agreed to revise the standards for regeneration procedures.